Edukasi Perlindungan Data Pribadi dalam Penggunaan Aplikasi Perbankan dan Media Sosial bagi Warga RW.011 Petukangan Utara Jakarta Selatan - Dewi Kusumaningsih; Sri Wahyuningsih; Rusdah Rusdah; Yulianawati Yulianawati; Devit Setiono; Yuni Kasmawati; Rizq Mas Galih Wibisono; Yoshua Alfia Agatha; Lutfi Daniah; Firdhan Happyanda (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The increasing use of digital banking applications and social media has heightened the risk of personal data misuse due to limited public awareness of digital security. This community service program aimed to improve community knowledge and practical skills in protecting personal data when using digital banking applications and social media among residents of RW 011, Petukangan Utara, South Jakarta. The program was conducted on February 13, 2026, involving 35 participants consisting of neighborhood administrators, Family Welfare Movement (PKK) members, and youth organization representatives. The program adopted a Participatory Action Research (PAR) approach combined with a Community-Based Education strategy through needs assessment, participatory planning, educational sessions, demonstrations, mentoring, and evaluation. The results showed improved participant awareness of protecting one-time passwords (OTP), using stronger passwords, enabling two-factor authentication, adjusting social media privacy settings, and recognizing phishing attempts. In addition, a Digital Literacy WhatsApp Group was established to support continuous learning within the community.